Effectiveness of Midwifery Training Update on Midwife Knowledge Improvement in Midwifery Services in Magetan - Nani Surtinah; Sunarto Sunarto (Humanistic Network for Science and Technology (HNST), 2021)
2Department of Midwifery, Poltekkes Kemenkes Surabaya, Indonesia; sunartoyahyamuqaffi@gmail.com ABSTRACT One of the efforts made to improve the knowledge, skills and competence of midwives is the Midwifery Update training. This study aims to determine the effectiveness of midwifery update training on increasing knowledge of midwives in midwifery services. The study design was a post-test only control group design. The population consisted of an experimental group of 41 people and a control group of 41 people. The experimental group had the midwifery update training in 2019, while the control group was midwives who had never attended midwifery update training in 2019. The experimental group and the control group were selected by using cluster sampling technique after that the sample selection used simple random sampling. Data analysis was used independent samples t -test. The mean knowledge results of the midwifery update group that had never attended midwifery update training was 55.11, while the mean knowledge results of the midwifery update group knowledge was 75.19. Based on the independent t-test, it was found that the t-count results were -8,987 with a p-value of 0.000 (